A new species of Kosteletzkya (Hibisceae, Malvoideae, Malvaceae) and notes on a second species, both from eastern Democratic Republic of the Congo - Blanchard, Jr., Orland J. Blanchard, Jr. (Phytotaxa, 2013)
A new species, Kosteletzkya rotundalata, is described from northeastern Democratic Republic of the Congo. A second species, K. borkouana, originally characterized as endemic to northern Chad, is here documented from several localities in the Albertine Rift of eastern Democratic Republic of the Congo.